2012
DOI: 10.1158/1078-0432.ccr-11-2175
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Biomarkers as Predictors of Outcome in Patients with Advanced Hepatocellular Carcinoma

Abstract: Purpose: Validated biomarkers of prognosis and response to drug have not been identified for patients with hepatocellular carcinoma (HCC). One of the objectives of the phase III, randomized, controlled Sorafenib HCC Assessment Randomized Protocol (SHARP) trial was to explore the ability of plasma biomarkers to predict prognosis and therapeutic efficacy. Experimental Design: In SHARP, 602 patients with advanced HCC were randomized to receive either oral sorafenib 400 mg twice a day per os or matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
470
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(495 citation statements)
references
References 52 publications
22
470
2
1
Order By: Relevance
“…Therefore, it is important to identify the best prognostic factors that can predict response to sorafenib. Certain studies showed that serum VEGF concentration and extracellular signal-regulated kinase levels were good predictors (26,27); however, other surrogate biomarkers must be explored to evaluate prognosis or the efficacy of treatment with sorafenib HCC. In the present study, the patients were restricted to those with BCLC stage C or BCLC stage B but who had previously experienced TACE failure, for whom sorafenib is the major treatment method (28).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to identify the best prognostic factors that can predict response to sorafenib. Certain studies showed that serum VEGF concentration and extracellular signal-regulated kinase levels were good predictors (26,27); however, other surrogate biomarkers must be explored to evaluate prognosis or the efficacy of treatment with sorafenib HCC. In the present study, the patients were restricted to those with BCLC stage C or BCLC stage B but who had previously experienced TACE failure, for whom sorafenib is the major treatment method (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, patients' response is modest, and sorafenib treatment is associated with side effects (3)(4)(5)(6)(7)(8). Thus, several studies looked for predictive markers for sorafenib response (9)(10)(11), yet no such biomarkers have entered the clinical setting. Predictive biomarkers, identifying patient subsets to guide treatment choices, are usually based on distinct pathogenetic mechanisms, and are the cornerstone of personalized medicine ( 12,13 ).…”
Section: Introductionmentioning
confidence: 99%
“…10 , 16 ). Although VEGFRs were postulated as mediators of sorafenib response in HCC, testing for VEGF-A serum levels was not found to be predictive of sorafenib treatment success ( 10 ). Moreover, bevacizumab, an antibody against VEGF-A, only shows minimal responses in HCC (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of hepatocellular carcinoma (HCC) has rapidly increased in the last decade to reach the sixth most common cancers worldwide (4 ) . The evolution of compensated and decompensated liver cirrhosis has been clearly defined in HCV infected patients (5) . The compensated disease often remains asymptomatic for many years , allowing a normal quality of life .…”
Section: Introductionmentioning
confidence: 99%